Ultrastructural variation tune wing coloration of a moth Asota caricae Fabricius, 1775. Issue 6 (December 2017) - Mishra, Monalisa; Nayak, Nibedita; Sahoo, Harekrushna
Graphical abstract: Highlights: Asota caricae possess both concealing as well as disruptive colouration in it's wing. The forewing possesses UV signal for intraspecific signal communication. The ventral region of the forewing share similar pattern with dorsal forewing. The wing coloration observed in the wing is due to minor variation in ultrastructure present within the wing. Abstract: Butterflies and moths develop highly ordered coloration in their wing for signal transmission. We have investigated the ultrastructural arrangement of wing coloration of a moth Asota caricae, applying light, optical polarized, and scanning electron microscopy, and spectrophotometry. The forewing of the moth is brown in color with a white spot at the center. The hindwing is golden yellow in color with many black patches in it. The ventral part of the forewing and dorsal hindwing share the similar color pattern. The ventral part of the hindwing has dull coloration in comparison to the dorsal one although the pattern remains same. The spectrometry analysis reveals various patterns of absorbance and reflectance spectra for various colors. The peak observed for various colors remain same although the intensity of peak changes. Bright colors possess highly ordered structures whereas irregular structures are found in dull colored scales. The color variation observed due to dorsal and ventral part of the wing is due to the minute difference observed in terms of ultrastructural arrangement revealed by scanning electron microscope. The color pattern of A. caricae is due to variation of microstructures present within the scale.